2017
DOI: 10.1002/uog.17351
|View full text |Cite
|
Sign up to set email alerts
|

Impact of aspirin on trophoblastic invasion in women with abnormal uterine artery Doppler at 11–14 weeks: a randomized controlled study

Abstract: In women with defective trophoblastic invasion, as reflected by abnormal UtA Doppler, low-dose aspirin started in the first trimester does not have a significant effect on UtA impedance as pregnancy progresses; however, the study was underpowered to detect potential small effects . Copyright © 2016 ISUOG. Published by John Wiley & Sons Ltd.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
38
1
5

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(46 citation statements)
references
References 37 publications
2
38
1
5
Order By: Relevance
“…Following review of the abstracts, 119 potentially suitable trials were selected for full review. Of these, 40 studies involving 34 807 participants, met the inclusion criteria and were included in the final analysis (Figure ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Following review of the abstracts, 119 potentially suitable trials were selected for full review. Of these, 40 studies involving 34 807 participants, met the inclusion criteria and were included in the final analysis (Figure ).…”
Section: Resultsmentioning
confidence: 99%
“…None of the included studies reported on intrapartum fetal distress as an outcome. Due to the limited number of studies reporting the outcomes of operative vaginal birth, emergency CS for intrapartum fetal distress and birth asphyxia, these outcomes were not included in the meta‐analysis, and the individual study findings from the 10 studies reporting on these outcomes are presented in Table S1. Three studies reported on operative‐vaginal‐delivery rate, with all showing a reduced, albeit non‐significant, risk among women taking LDA.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The ultimate aim of screening is to identify patients for whom timely intervention may alter the natural progression of the disease. Although late FGR has not been specifically addressed, pooled data from randomized trials show that early administration of low-dose aspirin in women at high risk for pre-eclampsia can reduce the risk for fetal/neonatal weight < 10 th centile (pooled relative risk (RR) 0.76; 95% CI, 0.65-0.89) [29][30][31][32][33][34][35][36] and for fetal/neonatal weight < 3 rd centile (pooled RR 0.7; 95% CI, 0.49-0.99) 29,30,37,38 . Therefore, contingent screening enhances recognition of late FGR fetuses, but effective first-trimester detection would be needed for their potential prevention.…”
Section: Discussionmentioning
confidence: 99%